Volleyball and emotional health of students of pedagogical university - Y.Y. Muskharina; S.A. Chernobay (H.S. Skovoroda Kharkov National Pedagogical University, 2013)
The features of valueological pedagogical influence of volleyball lessons on the emotional state of pedagogical university students. In the experiment involved 96 students aged 18-20 years. It was found that 72% of students feel the satisfaction of most emotional needs during the game, 86.4% indicate a bright splash of feelings and a sense of mutual aid during the game, 24% of students met the best friends among the players section. 89.3% of students say that skill, sense of humor, energy, example and support of teacher (trainer) during exercise can affect the emotional state of the team and each student. Professional and personal qualities of the coach, to encourage students to employment volleyball positive impact on the physical, mental performance, improve attention, ability to work in a team, to overcome emotional stress, feelings of fatigue, improves emotional state of students.